Segregación ambiental en Santiago: 1952-1982 - Gross, Patricio; Rodríguez, Alfredo (Revista EURE - Revista de Estudios Urbano Regionales, 1988)
The authors analyze environmental characteristics of the municipal districts in which the city of Santiago is devided. The study extends from 1940 to 1983.Í It employs a set of indicators of environmental quality selected initially through the Delphi methodology.Í The study shows strong contrasts from one section of the city to another some of which seem to have deteriorated even further in the last few years.